Preliminary observations on rearing of the hill stream fish, Naziritor chelynoides (Mc Clelland) under pond environment - Joshi, K D (Indian Journal of Fisheries, 2011)
The present study was conducted to observe the general adaptability, growth and survival of a hill stream fish, Naziritor chelynoides, in the pond environment. The experimental fishes were caught from the rivulet Ladhiya in district Champawat (Uttaranchal), transported and reared in the experimental fishÂ farm at Chhirapani, Champawat from April 1998 to March 1999. A total of 45 fishes with body length ranging between 170-185 mm and corresponding weight of 39.5-46.0 g (average weight 43.5 g) were stocked in 2 cement ponds at a stocking density of 1.5 fish mâ€“2. The stock was fed with a laboratory formulated wet diet @ 1-3% of body weight. On completion of the experiment, the fish attained 195-230 mm body length with corresponding weight between 71.0-89.5 g (77.66 g) with an overall growth rate of 0.09 g dayâ€“1. The survival rate was 95.5%, in the ambient water temperature range between 4.5 - 24.3Â°C.